La critique des médias comme forme conflictuelle de méta-médiatisation - William Spano; Simon Gadras; Eva-Marie Goepfert (Communication)
During the last French presidential election, certain candidates were excluded from the March 20, 2017 debate on TF1, focusing attention anew on how ”small candidates” were treated by the media and raising the issue of how the media were covering the campaign, what their relation was with political actors, and more broadly, what their role was in democratic life. The authors describe this process as one of meta-mediatization. The corpus for this study comprises everything that was written and said about the argument between Nicolas Dupont-Aignan and Groupe TF1 regarding his exclusion from the March 20 debate in favour of the five candidates who were leading in the polls.